New species and records of phytoptid mites (Acari: Eriophyoidea: Phytoptidae) on sedges (Cyperaceae) from the Russian Far East - Chetverikov, Philipp E. (Zootaxa, 2016)
Two new phytoptine species, Oziella virgata n. sp. and O. ovalis n. sp., were collected from the Russian Far East on sedges, Carex appendiculata (Trautv. & C.A. Mey) Kükenthal and Kobresia myosuroides (Villars) Fiori, respectively, and are described herein using conventional light microscopy (LM) and confocal laser scanning microscopy (CLSM). In addition, Oziella cf. rigida (Roivainen 1950) was recorded from Carex scita var. riishirensis (Franch.) Kük. in the Kamchatka Peninsula whilst Novophytoptus rostratae Roivainen 1947 was found on Carex saxatilis L. and C. appendiculata in the Sakha Republic (Yakutia) of Russia and Carex soczavaeana Gorodkov on the Kamchatka Peninsula. Oziella virgata n. sp. has a unique rod-like seta u′ on the medial-lower surface of tarsi I & II, a character not previously described in eriophyoid mites. Additionally, the position of setae 3a in nymphs and females differs: these are located on the same annulus as tubercles of setae c2 in nymphs whereas in females, those are situated notably ahead of tubercles c2 (closer to coxae II). Males of O. virgata n. sp. possess a well-developed genital coverflap, resembling that of Mackiella reclinata Chetverikov & Craemer, 2014, Pentasetacus araucariae (Schliesske, 1985) and Loboquintus subsquamatus Chetverikov & Petanović, 2013. The original slidemounted specimens of the new Oziella species described herein were inappropriate for LM study. However, CLSM microscopy images obtained prior to remounting were sharp enough for diagnostic purposes indicating that this is a useful method for studying poor quality specimens which may otherwise be difficult to remount or, in some cases, are very rare.